Strategi Pemasaran Lembaga Pendidikan Islam Berbasis Boarding School dalam Mempertahankan Animo Masyarakat di Pondok Pesantren - Andi Kurniawan; Zainal Abidin; Mgs. Nazarudin Nazarudin (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study discusses the supporting and inhibiting factors in the implementation of a boarding school-based marketing strategy for Islamic education services at Pondok Pesantren al-Ittifaqiah Indralaya. The type of research used is field research (filed research) using a case study method approach that is descriptive qualitative. This study found several findings, firstly Al-Ittifaqiah Islamic Boarding School uses a strategy to win the competition, tactical strategy and value strategy which includes a mass marketing approach (mass marketing), Educational services are targeted to all groups, provide various excellent programs, carry out direct promotions. and indirectly, having superior human resources, always innovating in educational products and making it easier for students to continue their studies abroad. Second, the inhibiting factors in implementing the marketing strategy of boarding school-based Islamic education services at Pondok Pesantren al-Ittifaqiah Indralaya are having a clear segment, very good al-Ittifaqiah Brand, public and alumni trust is still relatively high, and advances in information technology. The obstacle in implementing the marketing strategy for boarding school-based Islamic education services is that the number of human resources is not optimal, which has an impact on the less than optimal management of students in terms of monitoring student delinquency and cleanliness of the dormitory environment. In addition, the large number of students, not accompanied by complete facilities and infrastructure, has an impact on the learning and teaching process, such as some groups who still use mosques and dormitories as classrooms.